If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5h + 7 = 20 Reorder the terms: 7 + 5h = 20 Solving 7 + 5h = 20 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5h = 20 + -7 Combine like terms: 7 + -7 = 0 0 + 5h = 20 + -7 5h = 20 + -7 Combine like terms: 20 + -7 = 13 5h = 13 Divide each side by '5'. h = 2.6 Simplifying h = 2.6
| 2/7(4m-8)=12 | | -3(6s+6)= | | 2-3/5x=1/5x | | 4x-1=9x-11 | | 8*7*6*2*90*987*453*x= | | (-5s^2f-2sf^2+3sf)-(-7s^2f-12sf^2-4sf)= | | 7x+3y=mforx | | 8*7*6*2*90*987*453x= | | 8*7*6*2*90*987*453= | | A=2x^2-10x | | -60w^2-550wz+500z^2=0 | | X-12.5=18.1 | | 6v-12=4v-3 | | 6v-13=4v-3 | | 13x-8(3y-2)=-7x-5(12-3x) | | 3(x+8)+7=8x-5(x-3) | | 2u+1=3u-8 | | 3v-5=-48+-40v | | (3x^2y-3xy+6xy^2)-(2x^2y+4xy+5xy^2)= | | x^2-36x+243=0 | | 7+4(5x-5)=7-3(2x+1) | | 13y-8(3y-2)=-7y-5(12-3y) | | 11x-24=3x | | 3x^2+3x-70=0 | | .3(3z+7)+22.5=.6(3z-4) | | 9b^2-88b-20= | | 13(y+5)=8y+105 | | .3x-5=0.1(x+30) | | 3x^3+17x^2-30x-144=0 | | 2n-5=90 | | 2*6/5 | | .95y+2=y-.5 |